Expression Profiles of ANGUSTIFOLIA3 and SHOOT MERISTEMLESS, Key Genes for Meristematic Activity in a One-Leaf Plant Monophyllaea glabra, Revealed by Whole-Mount In Situ Hybridization - Kinoshita, Ayaka; Koga, Hiroyuki; Tsukaya, Hirokazu (Frontiers in Plant Science, 2020)
Members of the genus Monophyllaea are unique in that they produce no new organ during the vegetative phase in the shoot; instead, one of the cotyledons grows indeterminately. The mechanism of this unique trait is unclear, in part because of the lack of suitable assessment techniques. We therefore established a whole-mount in situ hybridization technique, a powerful means of examining spatial patterns in gene expression, for Monophyllaea glabra. By using this, we examined the expression pattern of a SHOOT MERISTEMLESS (STM) ortholog, which is indispensable for the formation and maintenance of the shoot apical meristem (SAM) in typical angiosperms. Expression was confined to the groove meristem (GM), which corresponds to the SAM. We also assessed the expression pattern of ANGUSTIFOLIA3 (AN3), a key promoter for cell division in the leaf meristem. It was expressed not only in basal meristem (BM) tissue with active cell division in the basal part of the growing cotyledon but also in the GM. The findings suggest that the unusual gene expression pattern of the GM underpins the fuzzy morphogenesis of Monophyllaea.